Differences in Leisure Physical Activity Participation in Children with Typical Development and Cerebral Palsy. (3rd April 2021) - Vila-Nova, Fabio; Dos Santos Cardoso de Sá, Cristina; Oliveira, Raul; Cordovil, Rita
ABSTRACT: Aim: To compare participation in leisure physical activities in children with typical development (TD) and cerebral palsy (CP). Methods: A total of 170 children with TD (n = 101) and CP (n = 69) aged 8 to 18 years reported participation in 16 extracurricular physical activities. Non-parametric statistics examined differences between groups. Results: Children with TD participated more frequently in individual physical activities ( p = .018), team sports ( p = .026), and bicycling ( p = .001), and less in horseback riding ( p = .031) than children with CP in GMFCS II–V. The differences between children with TD and CP in GMFCS I and within the CP group were not statistically significant. We did not find differences between groups in enjoyment. Conclusion: Children with CP in GMFCS II–V tend to participate less in leisure physical activities that require higher motor and perceptual skills. Support in the adaptation of physical recreation and sports may help improve participation.